2014
DOI: 10.1371/journal.pone.0114551
|View full text |Cite
|
Sign up to set email alerts
|

Genome Annotation Provides Insight into Carbon Monoxide and Hydrogen Metabolism in Rubrivivax gelatinosus

Abstract: We report here the sequencing and analysis of the genome of the purple non-sulfur photosynthetic bacterium Rubrivivax gelatinosus CBS. This microbe is a model for studies of its carboxydotrophic life style under anaerobic condition, based on its ability to utilize carbon monoxide (CO) as the sole carbon substrate and water as the electron acceptor, yielding CO2 and H2 as the end products. The CO-oxidation reaction is known to be catalyzed by two enzyme complexes, the CO dehydrogenase and hydrogenase. As expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…gelatinosus was studied from the point of view of its ability to catalyze water-gas shift reaction [48]. Another study [29] showed that HupSL deletion is an effective way of providing hydrogen production from CO, but nothing could be said about the properties of HupSL hydrogenase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gelatinosus was studied from the point of view of its ability to catalyze water-gas shift reaction [48]. Another study [29] showed that HupSL deletion is an effective way of providing hydrogen production from CO, but nothing could be said about the properties of HupSL hydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Rubrivivax gelatinosus was subjected to deletion of HupSL genes in order to increase hydrogen yield. This work by Wawrousek and colleagues mentioned presence of supernumerary cysteines in this enzyme, drawing interest to it from the point of view of oxygen tolerance [29]; the work by Manness and co-workers demonstrated presence of oxygen-tolerant hydrogenase linked to CO metabolism of this bacterium [30].…”
Section: Introductionmentioning
confidence: 98%
“…93 In addition, R. gelatinosus has been described as a very quickly growing facultative photoheterotrophic microorganism. 47 Paracoccus aminophilus and R. saidenbachensis can be considered very adaptable microorganisms with a broad range of different respiration pathways 94 and the ability to utilize various secondary algal metabolites, such as sugar alcohols, 48 which can be considered constantly present in the EPS matrix, due to secretion by algal cells or as a result of cell death and lysis. This metabolic versatility might be an essential prerequisite for these microbes to utilize different niches, eg, gradient zones, in the biofilm system, which become increasingly complex due to diatom development.…”
Section: Role Of Microorganisms In Biofilm Matrixmentioning
confidence: 99%
“…45,46 Besides these ubiquitous occurring microorganisms, several bacterial species were identified that were independent of LI. However, four species dominated in biofilms grown under high LI: Rubrivivax gelatinosus 47 and Rhodoferax saidenbachensis 48 in early development stages and Neosynechococcus sphagnicola 49 and Leptolyngbya spp. 50 in matured biofilms.…”
mentioning
confidence: 99%
“…Mutants lacking the uptake hydrogenase have not been reported in the photosynthetic species of betaproteobacteria, although H 2 production induced by carbon monoxide (CO) was recently studied in Rubrivivax gelatinosus strain CBS (Vanzin et al, 2010). This reaction is catalyzed by the NiFe-type hydrogenase, as has been shown in the species of alphaproteobacteria, Rhodospirillum rubrum (Fox et al, 1996), and is a side reaction of the oxidation of CO to CO 2 by the CO dehydrogenase (Vanzin et al, 2010;Wawrousek et al, 2014). It is of interest to utilize various photosynthetic species of metabolically versatile proteobacteria and to expand the possibility of their applications.…”
Section: Introductionmentioning
confidence: 99%